2008
DOI: 10.3892/ijmm.21.4.453
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of apolipoprotein E deficiency in cerebral aneurysm formation

Abstract: Abstract. Subarachnoid hemorrhage due to the rupture of a cerebral aneurysm is a life-threatening disease. Despite this, the detailed mechanisms underlying the initiation and progression of cerebral aneurysm are unclear. The relation of hypercholesterolemia and apolipoprotein E (ApoE) to cerebral aneurysm formation, has been unclear until now. We used, in the present study, a previously established cerebral aneurysm model of rats and mice whose histological features were closely similar to human cerebral aneur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Further, 16% of C57BL/6 wild‐type mice developed advanced intracranial aneurysms compared to 17% of ApoE −/− mice. Similarly, 32% of wild‐type mice developed early aneurysmal changes compared to 28% of ApoE −/− mice . This was in agreement with a clinical report which showed that ApoE alleles were not associated with the incidence of intracranial aneurysm .…”
Section: The Molecular Mechanisms Involved In Intracranial Aneurysm Dsupporting
confidence: 90%
See 2 more Smart Citations
“…Further, 16% of C57BL/6 wild‐type mice developed advanced intracranial aneurysms compared to 17% of ApoE −/− mice. Similarly, 32% of wild‐type mice developed early aneurysmal changes compared to 28% of ApoE −/− mice . This was in agreement with a clinical report which showed that ApoE alleles were not associated with the incidence of intracranial aneurysm .…”
Section: The Molecular Mechanisms Involved In Intracranial Aneurysm Dsupporting
confidence: 90%
“…Twenty‐two publications that report the use of mouse models of intracranial aneurysm were identified by searching the PubMed database . In these papers, five mouse models of intact intracranial aneurysm (see the following sections) and two mouse models of ruptured intracranial aneurysm (see the following sections) have been reported (Table ).…”
Section: Mouse Models Of Intracranial Aneurysmmentioning
confidence: 99%
See 1 more Smart Citation
“…In pathological studies, CA is not accompanied by atherosclerosis (26). Furthermore, in ApoE knockout mice, which presented marked hypercholesterolemia, CA formation was not changed, indicating that hypercholesterolemia, a main risk factor of atherosclerosis, might not be responsible for CA formation (27). MMP-9 is a proteinase with both collagenase and elastase activity, and plays a critical role in both CA (25) and AAA formation (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…In the pathogenesis of aneurysm formation, there are similarities and differences between abdominal aortic aneurysm (AAA) and cerebral aneurysm (CA). AAAs are shown to initiate and progress from arteriosclerotic changes, but there are no apparent arteriosclerotic changes in saccular aneurysm walls2). However, the fusiform and giant CA have different underlying pathologies, hemodynamics, anatomical distributions and natural histories when compared to the saccular CA15).…”
Section: Introductionmentioning
confidence: 99%